Regulating the Natural Resources in the Antarctic Region: A Historical Review - Basberg, Bjørn L (The political economy of resource regulation : an international and comparative history, 1850-2015, 2019)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalindustri; naturressurser; pelagisk; økonomi

Den siste olje - Berge, Aslak (Octavian forlag AS, 2019)
Over seks tiår fylte glinsende fett fra hundretusenvis av hval råstoffbehov til multinasjonale konserners margarin- og såpeprodukter. Hoffleverandørene var norske hvalfangere. Fra spekkjelene like etter århundreskiftet ble fyrt opp på Sør-Georgia til det flytende kokeriet Kosmos IV ankret opp i Sandefjord på slutten av 1960-tallet, skulle hvalfangst dominere og forme utviklingen av finansmarked, konsumvarer og kapitalisme i Norge. Dette er en fortelling om eksplosivt voksende rikdom og merkevarebygging, men også en biologisk tragedie. Et nådeløst møte mellom jordens største dyr, effektiv fangsteknologi og konsumindustri. Dette er en flerfasettert historie om et kapitalfattig lands industrialisering, skattesky redere og multinasjonale fettkjemper, men også om ubegrensede offer og tap. Om norsk polarimperialisme og globalt salg utfordret av stormakter og skiftende konjunkturer. Dette er historien om "Den siste olje".
Keywords: Norge; Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk; økonomi

A continent of and for whiteness?: “White” colonialism and the 1959 Antarctic Treaty - Mancilla, Alejandra (Polar Record, 2019)
There are at least four ways in which Antarctic colonialism was white: it was paradigmatically performed by white men; it consisted in the taking of vast, white expanses of land; it was carried out with a carte blanche (literally, “blank card”) attitude; and it was presented to the world as a white, innocent adventure. While the first, racial whiteness has been amply problematised, I suggest that the last three illuminate yet other moral wrongs of the Antarctic colonial project. Moreover, they might be constitutive of a larger class of “white” colonialisms beyond the White Continent.
Keywords: Antarktis; historie; politikk; samfunnsfag

Roald Amundsen’s sled dogs : the sledge dogs who helped discover the South Pole - Tahan, Mary R (Springer, 2019)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Proterozoic evolution of central Dronning Maud Land (East Antarctica) from Rodinia to Gondwana - Wang, Cheng-Cheng; Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas ([ISAES], 2019)
Keywords: Dronning Maud Land; geologi

Polarårboken Glacier (Polarboken, 2018)
Keywords: Antarktis; geografi; glasiologi

I Roald Amundsens fotspor til Sydpolen med besøk på Bettytoppen - Furholt, Astrid (Polarboken, 2018)
Keywords: Antarktis; ekspedisjoner; historie

Ice-rise stratigraphy reveals changes in surface mass balance over the last millennia in Dronning Maud Land - Goel, Vikram; Martín, Carlos; Matsuoka, Kenichi (Journal of Glaciology, 2018)
We use ice flow modelling to simulate the englacial stratigraphy of Blåskimen Island, an ice rise in Dronning Maud Land and elucidate the evolution of this data-sparse region. We apply a thermo-mechanically coupled Elmer/Ice model to a profile along flowlines and through the ice-rise summit, where surface mass balance (SMB), flow velocity and ice stratigraphy were recently measured. We conclude that: (i) the ice rise is presently thickening at a rate of 0.5~0.6 m ice equivalent per year (mieq a−1), which is twice an earlier estimate using the field data and the input–output method; (ii) present thickening started 20–40 years in the past, before which the ice rise was in a steady state; (iii) SMB contrast between the upwind and downwind slopes was stronger than the present value by ~23% (or 0.15 mieq a−1) prior to ~1100 years ago. Since then, this contrast has been decreasing overall. We surmise that these SMB changes are likely a result of synoptic-scale atmospheric changes, rather than local atmospheric changes controlled by local ice topography. Our technique effectively assimilates geophysical data, avoiding the complexity of ice flow beneath the ice divide. Thus, it could be applied to other ice rises to elucidate the recent glacial retreat.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Antarctic environmental protection: strengthening the links between science and governance - Hughes, Kevin A; Constable, Andrew; Frenot, Yves; López-Martinez, Jerónimo; McIvor, Ewan; Njåstad, Birgit; Terauds, Aleks; Liggett, Daniela; Roldan, Gabriela; Wilmotte, Annick; Xavier, José C (Environmental Science & Policy, 2018)
The Antarctic has significant environmental, scientific, historic, and intrinsic values, all of which are worth protecting into the future. Nevertheless, the area is subject to an increasing level and diversity of human activities that may impact these values within marine, terrestrial and cryosphere environments. Threats to the Antarctic environment, and to the aforementioned values, include climate change, pollution, habitat destruction, wildlife disturbance and non-native species introductions. Over time, a suite of legally binding international agreements, which form part of the Antarctic Treaty System (ATS), has been established to help safeguard the Antarctic environment and provide a framework for addressing the challenges arising from these threats. Foremost among these agreements are the Protocol on Environmental Protection to the Antarctic Treaty and the Convention on the Conservation of Antarctic Marine Living Resources. Many scientists working in Antarctica undertake research that is relevant to Antarctic environmental policy development. More effective two-way interaction between scientists and those responsible for policy development would further strengthen the governance framework, including by (a) better communication of policy makers’ priorities and identification of related science requirements and (b) better provision by scientists of ‘policy-ready’ information on existing priorities, emerging issues and scientific/technological advances relevant to environmental protection. The Scientific Committee on Antarctic Research (SCAR) has a long and successful record of summarizing policy-relevant scientific knowledge to policy makers, such as through its Group of Specialists on Environmental Affairs and Conservation (GOSEAC) up to 2002, currently the SCAR Standing Committee on the Antarctic Treaty System (SCATS) and recently through its involvement in the Antarctic Environments Portal. Improvements to science-policy communication mechanisms, combined with purposeful consideration of funding opportunities for policy-relevant science, would greatly enhance international policy development and protection of the Antarctic environment.
Keywords: Antarktis; miljøvern

The relationship between coastal weather and foraging behaviour of chinstrap penguins, Pygoscelis antarctica - Lowther, Andrew D; Trathan, Phil; Tarroux, Arnaud; Lydersen, Christian; Kovacs, Kit M (ICES Journal of Marine Science, 2018)
There is increasing interest in using higher-trophic level predators as ecosystem indicators because their performance is presumed to be linked to the overall function of the ecosystem that supports them. In the southwest Atlantic sector of the Southern Ocean, Antarctic krill (Euphausia superba) supports huge predator populations as well as a growing commercial fishery. To utilize information from the ecosystem in an adaptive framework for sustainably managing krill catch levels, performance indices of krill predators have been proposed as a proxy for krill abundance. However, there are several potentially confounding sources of variability that might impact predator performance such as the effects of environmental variability and fishing pressure on krill availability at scales relevant to predators. In this context, our study capitalises on the occurrence of an unexpected El Niño event to characterise how environmental variability can drive changes in predator foraging behaviour. We demonstrate a clear link between coastal downwelling and changes in the at-sea habitat usage of chinstrap penguins (Pygoscelis antarctica) foraging in a local krill fishing area. Penguins tracked from their breeding colonies on Powell Island, Antarctic Peninsula, undertook fewer, longer foraging trips during the downwelling-affected season compared with the season where no such downwelling was detected, suggesting that changes in climate-driven oceanography may have reduced krill availability along the northern shelf of the island. Our study demonstrates that penguin foraging behaviour is modified by scale-dependent processes, which if not accounted for may result in erroneous conclusions being drawn when using penguins as bioindicators of krill abundance.
Keywords: Sørishavet; marinbiologi; meteorologi; ornitologi; pingviner; økologi

The moral limits of territorial claims in Antarctica - Mancilla, Alejandra (Ethics & International Affairs, 2018)
By virtue of the Antarctic Treaty, signed in 1959, the territorial claims to Antarctica of seven of the original signatories were held in abeyance or “frozen.” Considered by many as an exemplar of international law, the Antarctic Treaty System has come to be increasingly questioned, however, in a very much changed global scenario that presents new challenges to the governance of the White Continent. In this context, it is necessary to gain a clearer understanding of the moral weight of those initial claims, which stand (despite being frozen) as a cornerstone of the treaty. The aim of this article is to offer an appraisal of such claims, which may be divided into two main kinds: those grounded on some relevant link to the territory, and those grounded on official documents and geographical doctrines. After pointing to the limitations and challenges that they face, I conclude with some remarks about how this assessment ought to serve as a starting point to rethink the territorial status of Antarctica.
Keywords: Antarktis; historie; jus; politikk; ressurser

Kapten Roald Amundsen: I vargskinnspäls och textil. Blir först på Sydpolen - Norén, Karl-Gunnar (Polarfararnas kläder : på liv och död, 2018)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner; utstyr

Ground displacements on Bouvet Island using SAR Interferometry (18/2018) - Rouyet, Line; Lauknes, Tom Rune; Larsen, Yngvar; Norut (2018)
Based on 8 RADARSAT-2 Ultrafine scenes from December 2017 to June 2018, ground displacements close to the Norvegia research station of Bouvet Island have been measured using Synthetic Aperture Radar Interferometry (InSAR). The results show that loss of coherence related to erosion processes is affecting the coast west from the station. The mean velocity maps identify a well-defined unstable area south from Norvegia and by applying the Small Baseline Subset (SBAS) time-series InSAR method, we are able to provide time series during the considered time period. The results tend to indicate that the area north from the current location of Norvegia station is more stable.
Keywords: Bouvetøya; geovitenskap; interferometri

Psychological Hibernation in Antarctica - Sandal, Gro Mjeldheim; van deVijver, Fons J. R.; Smith, Nathan (Frontiers in Psychology, 2018)
Human activity in Antarctica has increased sharply in recent years. In particular during the winter months, people are exposed to long periods of isolation and confinement and an extreme physical environment that poses risks to health, well-being and performance. The present study aimed to gain a better understanding of processes contributing to psychological resilience in this context. Specifically, the study examined how the use of coping strategies changed over time, and the extent to which changes coincided with alterations in mood and sleep. Two crews (N = 27) spending approximately 10 months at the Concordia station completed the Utrecht Coping List, the Positive and Negative Affect Schedule (PANAS), and a structured sleep diary at regular intervals (x 9). The results showed that several variables reached a minimum value during the midwinter period, which corresponded to the third quarter of the expedition. The effect was particularly noticeable for coping strategies (i.e., active problem solving, palliative reactions, avoidance, and comforting cognitions). The pattern of results could indicate that participants during Antarctic over-wintering enter a state of psychological hibernation as a stress coping mechanism.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Hvaleventyret : hvordan vi nesten utryddet det største dyret som har levd - Tjernshaugen, Andreas (Kagge, 2018)
Historien om jakten på blåhvalen, verdens største dyr. Blåhvalen var nær ved å bli utryddet av den moderne hvalfangsten med raske båter, sprenggranater og harpunkanon. Lenge utgjorde Vestfold verdens hvalfangstsentrum, og på det meste forlot ti tusen norske menn familien og dro på hvalfangst i fremmede farvann. Det var et blodslit, og et eventyr. Helt fra starten kom det advarsler om at hvalene kunne bli utryddet. For blåhvalen var det på nære nippet. Underarten i Antarktis, som blir aller størst, regnes fortsatt som kritisk truet. I sluttspillet om blåhvalens skjebne ble Norge utfordret av både Storbritannia og Nazi-Tyskland, Japan og Sovjetunionen, som kastet seg inn i kampen om Sørishavets rikdommer. "Hvaleventyret" er en medrivende historie om blåhvalen og hvalfangsten. Den forteller om hvalenes årlige trekk mellom isen og varmere hav, om hvalfangernes livsfarlige pionerferder i polhavene, og om kampen for å redde de siste blåhvalene.
Keywords: Nordmenn; Norge; Sørishavet; dyrevern; hvaler; hvalfangst; hvalindustri; pelagisk; sjøpattedyr

Versatility of GC-Orbitrap mass spectrometry for the ultra-trace detection of persistent organic pollutants in penguin blood from Antarctica - Warner, Nicholas; Cojocariu, Cristian; Scientific, ThermoFisher (2018)
Using GC Orbitrap mass spectrometry to address analytical challenges with trace level detection of persistent organic pollutants in Antarctica.
Keywords: Antarktis; biologi; miljøgifter; pingviner; zoologi

A new compiled geological map of Dronning Maud Land, Antarctica - Abu-Alam, Tamer; Elvevold, Synnøve; Jacobs, Joachim; Myhre, Per Inge (Norsk Geologisk Forening (NGF), 2017)
Dronning Maud Land in East Antarctica represents the central part of the Gondwana supercontinent. Geological mapping and investigation of Dronning Maud Land have been carried out over the last 40-50 years. The existing geological maps of Dronning Maud Land are, for a large part, based on fairly old data, which makes these maps inhomogeneous. The maps are at different scales, contain different levels of details, and the standards for classification of the rock units may also differ between the maps. This limits the ability to use these map to draw an overview tectonic model of the evolution of Dronning Maud Land. Moreover, the existing topographic dataset from Dronning Maud Land is based on fairly old topographic maps (1960s), and there is a discrepancy between the topographic dataset and the more recent Landsat images. There are still unmapped areas.
Keywords: Dronning Maud Land; geologi

Sett fra luften - Berg, Thomas Reinertsen (Verdensteater : kartenes historie, 2017)
Keywords: ekspedisjoner; flyfotografering; karthistorie; kartlegging; kartografi

Exploring the Recovery Lakes region and interior Dronning Maud Land, East Antarctica, with airborne gravity, magnetic and radar measurements - Forsberg, Rene; Olesen, Arne; Jordan, Tom; Matsuoka, Kenny; Zakrajsek, Andres; Ghidella, Marta; Greenbaum, Jamin (Geological Society, London, Special Publications, 2017)
Long-range airborne geophysical measurements were carried out in the ICEGRAV campaigns, covering hitherto unexplored parts of interior East Antarctica and part of the Antarctic Peninsula. The airborne surveys provided a regional coverage of gravity, magnetic and icepenetrating radar measurements for major Dronning Maud Land ice stream systems, from the grounding lines up to the Recovery Lakes drainage basin, and filled in major data voids in Antarctic data compilations, such as AntGP for gravity data, ADMAP for magnetic data and BEDMAP2 for ice thickness data and the sub-ice topography. We present the first maps of gravity, magnetic and ice thickness data and bedrock topography for the region and show examples of bedrock topography and basal reflectivity patterns. The 2013 Recovery Lakes campaign was carried out with a British Antarctic Survey Twin Otter aircraft operating from the Halley and Belgrano II stations, as well as a remote field camp located at the Recovery subglacial Lake B site. Gravity measurements were the primary driver for the survey, with two airborne gravimeters (Lacoste and Romberg and Chekan-AM) providing measurements at an accuracy level of around 2 mGal r.m.s., supplementing GOCE (Gravity Field and Steady-State Ocean Circulation Explorer) satellite data and confirming an excellent sub-milligal agreement between satellite and airborne data at longer wavelengths.
Keywords: Dronning Maud Land; geofysikk; glasiologi

Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica - Goel, Vikram; Brown, Joel; Matsuoka, Kenichi (The Cryosphere, 2017)
The ice-shelf-fringed coast of Dronning Maud Land in East Antarctica contains numerous ice rises that influence the dynamics and mass balance of the region. However, only a few of these ice rises have been investigated in detail. Here, we present field measurements of Blåskimen Island, an isle-type ice rise adjacent to Fimbul Ice Shelf. This ice rise is largely dome shaped, with a pronounced ridge extending to the south-west from its summit (410 m a.s.l.). Its bed is mostly flat and about 100 m below the current sea level. Shallow radar-detected isochrones dated with a firn core reveal that the surface mass balance is higher on the south-eastern (upwind) slope than on the north-western (downwind) slope by ∼ 37 %, and this pattern has persisted for at least the past decade. Moreover, arches in radar stratigraphy suggest that the summit of the ice rise has been stable for ∼ 600 years. Ensemble estimates of the mass balance using the input–output method show that this ice rise has thickened by 0.12–0.37 m ice equivalent per year over the past decade.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Carsten Borchgrevink and the Southern Cross Expedition, 1898-1900 - Riffenburgh, Beau; Kløver, Geir O (Red.) (The Fram Museum, 2017)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Norway and the Antarctic - Stephenson, Robert B; [Barr, Susan] (The Erebus and Terror Press, 2017)
Keywords: Antarktis; Nordmenn; norske ekspedisjoner; polarfarere

At-Sea Distribution and Prey Selection of Antarctic Petrels and Commercial Krill Fisheries - Descamps, Sébastien; Tarroux, Arnaud; Cherel, Yves; Delord, Karine; Godø, Olaf Rune; Akiko, Kato; Krafft, Bjørn A; Lorentsen, Svein-Håkon; Ropert-Coudert, Yan; Skaret, Georg; Varpe, Øystein (PloS One, 2016)
Kommersielle fiskerier kan påvirke marine økosystemer og bestander av topp-predatorer som sjøfugl. I Sørishavet foregår et ekstensivt fiske etter Antarktisk krill (Euphausia superba), og dette er antatt å øke. En sammenligning av fordeling og uttak hos fiskeriene og tilsvarende hos topp-predatorene er nødvendig for å forutsi fiskerirelaterte påvirkninger på krillavhengige predatorer. I dette studiet kartla vi næringssøksområdene hos Antarktispetrell (Thalassoica antarctica) som hekker i verdens største koloni (Svarthammaren, Dronning Maud land) over en treårsperiode. Vi fant at det romlige overlappet mellom krillfiskerier og næringssøkende Antarktispetrell generelt var lite. Konkurranse mellom Antarktispetrell og krill-fiskerier er for tiden neglisjerbart, men kan øke hvis fiskeriet etter krill øker.
Keywords: Dronning Maud Land; Sørishavet; fiskeriforvaltning; krill; marinbiologi; ornitologi; økosystem

Den norsk-brittisk-svenska Antarktisexpeditionen (NSBX) - Holmlund, Per; Martinsson, Tyrone (Frusna ögonblick : svensk polarfotografi 1861-1980, 2016)
Keywords: Antarktis; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fotografi; fotohistorie; polarekspedisjoner

Delivering 21st century Antarctic and Southern Ocean science - Kennicutt, Mahlon C I I; Kim, Yeadong; Rogan-Finnemore, Michelle; Anandakrishnan, Sridhar; Chown, Steven L; Colwell, Steven (Antarctic Science, 2016)
The Antarctic Roadmap Challenges (ARC) project identified critical requirements to deliver high priority Antarctic research in the 21st century. The ARC project addressed the challenges of enabling technologies, facilitating access, providing logistics and infrastructure, and capitalizing on international co-operation. Technological requirements include: i) innovative automated in situ observing systems, sensors and interoperable platforms (including power demands), ii) realistic and holistic numerical models, iii) enhanced remote sensing and sensors, iv) expanded sample collection and retrieval technologies, and v) greater cyber-infrastructure to process ‘big data’ collection, transmission and analyses while promoting data accessibility. These technologies must be widely available, performance and reliability must be improved and technologies used elsewhere must be applied to the Antarctic. Considerable Antarctic research is field-based, making access to vital geographical targets essential. Future research will require continent- and ocean-wide environmentally responsible access to coastal and interior Antarctica and the Southern Ocean. Year-round access is indispensable. The cost of future Antarctic science is great but there are opportunities for all to participate commensurate with national resources, expertise and interests. The scope of future Antarctic research will necessitate enhanced and inventive interdisciplinary and international collaborations. The full promise of Antarctic science will only be realized if nations act together.
Keywords: Antarktis; forskning; vitenskap

Jason-ekspedisjonene 1892-1894, Antarctic-ekspedisjonen 1901-1904 - Larsen, Carl Anton; Kløver, Geir O (Red.) (Frammuseet, 2016)
Keywords: Antarctic ekspedisjonen; Antarktis; Carl Anton Larsen; D/S Antarctic; D/S Jason; Jason ekspedisjonene; Sørishavet; dagbok; ekspedisjoner; hvalfangere; hvalfangst; polarområdene

Gåten om Roald Amundsens varde på Bettyfjellet i Antarktis - Mehlum, Fridtjof (Polarboken, 2016)
Keywords: Antarktis; ekspedisjoner; historie

Polheim: teltet på Sydpolen - Melgård, Anne (Polarboken, 2016)
Keywords: Antarktis; ekspedisjoner; historie

Chinstrap and macaroni penguin diet and demography at Nyrøysa, Bouvetøya - Niemandt, Corne; Kovacs, Kit M; Lydersen, Christian; Dyer, Bruce M; Isaksen, Kjell; Hofmeyr, G J Greg; Mehlum, Fridtjof; de Bruyn, P J Nico (Antarctic Science, 2016)
Keywords: Bouvetøya; klimaendringer; krill; pelsseler; pingviner; plankton

"Big Science" for meteorologene - Nilsen, Yngve; Vollset, Magnus (Vinden dreier : meteorologiens historie i Norge, 2016)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi

Ice core evidence for a 20th century increase in surface mass balance in coastal Dronning Maud Land, East Antarctica - Philippe, Morgane; Tison, Jean-Louis; Fjøsne, Karen; Hubbard, Bryn; Kjær, Helle A; Lenaerts, Jan T M; Drews, Reinhard; Sheldon, Simon G; De Bondt, Kevin; Claeys, Philippe; Pattyn, Frank (The Cryosphere, 2016)
Ice cores provide temporal records of surface mass balance (SMB). Coastal areas of Antarctica have relatively high and variable SMB, but are under-represented in records spanning more than 100 years. Here we present SMB reconstruction from a 120 m-long ice core drilled in 2012 on the Derwael Ice Rise, coastal Dronning Maud Land, East Antarctica. Water stable isotope (δ18O and δD) stratigraphy is supplemented by discontinuous major ion profiles and continuous electrical conductivity measurements. The base of the ice core is dated to AD 1759 ± 16, providing a climate proxy for the past  ∼ 250 years. The core's annual layer thickness history is combined with its gravimetric density profile to reconstruct the site's SMB history, corrected for the influence of ice deformation. The mean SMB for the core's entire history is 0.47 ± 0.02 m water equivalent (w.e.) a−1. The time series of reconstructed annual SMB shows high variability, but a general increase beginning in the 20th century. This increase is particularly marked during the last 50 years (1962–2011), which yields mean SMB of 0.61 ± 0.01 m w.e. a−1. This trend is compared with other reported SMB data in Antarctica, generally showing a high spatial variability. Output of the fully coupled Community Earth System Model (CESM) suggests that, although atmospheric circulation is the main factor influencing SMB, variability in sea surface temperatures and sea ice cover in the precipitation source region also explain part of the variability in SMB. Local snow redistribution can also influence interannual variability but is unlikely to influence long-term trends significantly. This is the first record from a coastal ice core in East Antarctica to show an increase in SMB beginning in the early 20th century and particularly marked during the last 50 years.
Keywords: Dronning Maud Land; glasiologi; iskjerner

C.A. Larsen : explorer, whaler & family man - Riffenburgh, Beau (Red.); Kløver, Geir O (Red.) (The Fram Museum, 2016)
Keywords: Antarctic ekspedisjonen; Antarktis; Carl Anton Larsen; D/S Antarctic; D/S Jason; Jason ekspedisjonene; Weddellhavet; hvalfangere; hvalfangst; oppdagelsesreiser; polarforskning

Animals as instruments of Norwegian imperial authority in the interwar Arctic - Roberts, Peder; Jørgensen, Dolly (Journal for the History of Environment and Society, 2016)
During the first half of the twentieth century a number of individuals in Norway participated in the transfer of animals from both the Arctic to the Antarctic regions and vice versa. These projects may be conceptualized as a form of imperial acclimatization, following in the footsteps of earlier attempts to transplant both plants and animals from their indigenous ranges to new geographic locations for both practical and recreational purposes. Reindeer were introduced to the island of South Georgia before World War I as Norwegian whalers turned a space previously uninhabited by humans into the operational hub of a booming Antarctic whaling industry. The successful transplantation of reindeer was followed by less successful attempts to transfer muskoxen from Greenland to Svalbard and the Scandinavian mainland, penguins from the Antarctic to the coast of Norway, and dreams of transferring fur seals from south to north. We argue that these attempts constituted both practical attempts to “enrich” the fauna of discrete habitats, but also expressions of Norwegian authority over the polar regions at a time when imperial ambitions in both the Arctic and Antarctic had significant traction within Norway. The transplanted animals may thus be conceived as geopolitical instruments – mastery over fauna as being a means of expressing mastery over space.
Keywords: Antarktis; Bouvetøya; Norge; geopolitikk; hvalfangst; polarområdene

The canine explorers – the sled dogs who helped Roald Amundsen reach the South Pole - Tahan, Mary R (Journal of Antarctic Affairs, 2016)
One hundred Greenland dogs were purchased by Roald Amundsen from the Royal Greenland Trading Company in September 1909 ostensibly for a North Pole expedition, but secretly to use to reach the South Pole. Amundsen considered the dogs “equipment”. He was a complicated character in a very different time. And he compulsively pursued his mission. His actions perhaps are seen differently from the 21st century perspective and in light of our evolving attitude toward animals, especially dogs. This paper presents the facts of what happened concerning the sled dogs, using Amundsen’s own statements in his books, diaries, and letters, as well as the expedition members’ journal entries and personal letters. It focuses on the dogs who made Amundsen’s exploration possible, and who helped humankind discover the final undiscovered part of our world. Amundsen began his Norwegian expedition with 97 sturdy canine souls, who were taken on board the Fram near the coast of Kristiansand in August 1910. Through births and deaths on the ship during their five-month journey south, the dogs’ number swelled to 116 upon arrival in Antarctica. Adults and puppies alike withstood the roller-coaster ride of the Fram on the ocean waters, the heat of the tropics near the equator, and the freezing winter of Antarctica. Taking into account the birth of puppies on the ship and at their Antarctic home Framheim, the actual number of dogs involved in this significant moment in history doubles to over two hundred. But, after initially nurturing and protecting the dogs, Amundsen proceeded to cull them throughout the expedition, slaughtering those he deemed unnecessary or weak, and destroying those who had served their purpose. Amundsen began his South Pole trek in October 1911 with 52 brave canines, and returned with 11, as a result of unnatural, forced attrition. The dogs were nearly starved; at times when they were fed, it was the flesh of their fallen comrades they were given to line their empty stomachs. And yet the dogs all performed their roles brilliantly, even when death was their reward. The sled dogs were the heart and power of the South Pole expedition. The intent of this article is to shine a light on the dogs’ population, accomplishments, and sacrifices, and to give them their due recognition and place in history.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Frozen voices: Women, silence and Antarctica - Blackadder, Jesse (Antarctica : music, sounds and cultural connections, 2015)
This chapter explores a different kind of Antarctic silence: the silencing of certain stories and voices. It’s the silence of the earliest female travellers to Antarctica.The voices of the earliest female travellers are silent and their stories remain untold, partly because there’s no place for them in the dominant Antarctic narrative of exploration and conquest. Reimagining them through fiction is one way — though with potential pitfalls — to ‘unfreeze’ those stories.
Keywords: Antarktis; Nordmenn; ekspedisjoner; kvinner; oppdagelsesreiser

The WEGAS / GEA IV Geophysical Survey in eastern and southern Dronning Maud Land - Eagles, Graeme; Ruppel, Antonia; Steinhage, Daniel; Jokat, Wilfried; Läufer, Andreas; Jacobs, Joachim ([German Society for Polar Research], 2015)
The Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI) and the Federal Institute for Geosciences and Natural Resources (BGR) collected around 150 hours of new gravity, magnetic and ice-penetrating radar data from east and south of Princess Elisabeth station in Dronning Maud Land between 2013 and 2015. Survey lines were spaced 10 km apart. The 2013/2014 and 2014/2015 used different gravimeters; a LaCoste and Romberg AirSea gravimeter (LCR) at constant barometric altitude and a Gravimetric Technologies GT2A gravimeter at constant ground separation. Both surveys used a Scintrex Cs-3 caesium vapour magnetometer mounted in a tail boom with compensation for the airframe calculated using a fuselage-mounted three-component fluxgate magnetometer. The GT2A gravity data reflect the effects of short-wavelength density contrasts between basement rocks and the ice sheet more reliably than the LCR data. Cross-over analysis suggests the repeatability of data collection with the GT2A lies at the sub-milliGal level. A broad subglacial channel that separates eastern Sør Rondane from the Yamato Belgica Mountains is evident in the gravity data. In the south of the survey region, the data reveal a dendritic pattern of subglacial valleys that converge towards the SW. Strong NS-trending magnetic anomalies coincide with the Yamato-Belgica Mountains. Further west, subtler ESE-trending anomalies confirm proposals that the SE Dronning Maud Land province continues into the region south of eastern Sør Rondane. An unexpected feature of both data sets is the apparent termination of the anomaly patterns associated with the province at a NNW-trending anomaly running south of Princess Elisabeth.
Keywords: Dronning Maud Land; geofysikk; geovitenskap

East Antarctica and supercontinent configuration: the Dronning Maud Land perspective - Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas; Jokat, Wilfried (Japan Geoscience Union, 2015)
The geology of East Antarctica and its correlation in major supercontinents is highly speculative, since only a very small part of it is exposed. Therefore a better connection between geology and geophysics is needed in order to correlate exposed regions with ice-covered, geophysically-defined, blocks. In Dronning Maud Land (DML), two distinct late Mesoproterozoic/early Neoproterozoic tectono-metamorphic provinces appear, separated by the major, NE-trending Forster Magnetic Anomaly and South Orvin Shear Zone. To the west of this lineament, the Maud Belt has clear affinities with Grenville-age continent-continent mobile belts. East of the Forster Magnetic Anomaly, juvenile rocks with early Neoproterozoic age (Rayner-age) and an accretionary character crop out. The international GEA-II expedition (2012) targeted a white spot on the geological map immediately to the E of the Forster Magnetic Anomaly. This area allows the characterization and ground-truthing of a large and mostly ice-covered region, the SE DML Province that had previously been interpreted as an older cratonic block. However, new SHRIMP/SIMS zircon analyses and their geochemistry indicates that the exposed basement consists of a ca. 1000-900 Ma juvenile terrane that is very similar to rocks in Sor Rondane. It lacks significant metamorphic overprint at the end of crust formation, but it shows medium to high-grade overprinting between ca. 630-520 Ma, associated with significant felsic melt production, including A-type granitoid magmatism. Therefore, the aeromagnetically distinct SE DML province does neither represent the foreland of a Late Neoproterozoic/EarlyPaleozoic mobile belt, nor a craton, as has previously been speculated. It more likely represents the more juvenile, westward continuation of Rayner-age crust (1000-900 Ma). To the west it abuts along the NE-trending Forster Magnetic Anomaly. The latter is interpreted as a suture, which separates typical Grenville-age crust of the Maud Belt (ca. 1200-1030 Ma) to the W from Rayner-age crust to the E. Therefore the larger eastern part of DML has clearly Indian affinities. Its juvenile character with a lack of metamorphic overprint at the end of crust formation points to an accretionary history along this part of the Indian segment of Rodinia, immediately following final Rodinia assembly.
Keywords: Dronning Maud Land; geofysikk; geologi

Modern foraminifera assemblages in the Amundsen Sea Embayment - Jernas, Patrycja Ewa; Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Forwick, Matthias; Rasmussen, Tine Lander; Mackensen, Andreas; Schröder, Michael; Smith, James; Klages, Johann Philipp; Szczucinski, W (Norsk Geologisk Forening (NGF), 2015)
The West Antarctic Ice Sheet (WAIS) is considered the most unstable part of the Antarctic Ice Sheet. As the WAIS is mostly grounded below sea level, its stability is of great concern. A collapse of large parts of the WAIS would result in a significant global sea-level rise. At present, the WAIS shows dramatic ice loss in its Amundsen Sea sector, especially in Pine Island Bay. Pine Island Glacier (PIG) is characterised by fast flow, major thinning and rapid grounding-line retreat. Its mass los over recent decades is generally attributed to melting caused by the inflow of warm Circumpolar Deep Water (CDW). Future melting of PIG may result in a sea level tipping point, because it could trigger widespread collapse of the WAIS, especially when considering ongoing climate change.
Keywords: Sørishavet; geologi; innlandsis; klimaendringer

Modern foraminifera assemblages in the Amundsen Sea Embayment - Jernas, Patrycja Ewa; Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Rasmussen, Tine Lander; Forwick, Matthias; Mackensen, Andreas; Schröder, Michael; Smith, James; Klages, Johann Philipp (2015)
The West Antarctic Ice Sheet (WAIS) is considered the most unstable part of the Antarctic Ice Sheet. As the WAIS is mostly grounded below sea level, its stability is of great concern. A collapse of large parts of the WAIS would result in a significant global sea-level rise. At present, the WAIS shows dramatic ice loss in its Amundsen Sea sector, especially in Pine Island Bay. Pine Island Glacier (PIG) is characterised by fast flow, major thinning and rapid grounding-line retreat. Its mass los over recent decades is generally attributed to melting caused by the inflow of warm Circumpolar Deep Water (CDW). Future melting of PIG may result in a sea level tipping point, because it could trigger widespread collapse of the WAIS, especially when considering ongoing climate change.
Keywords: Sørishavet; geologi; innlandsis; klimaendringer

The great white silence : den offisielle filmen om Robert Falcon Scotts sydpolekspedisjon og en vurdering av ekspedisjonen - Lund, Vidar (Maritimt Magasin Historie, 2015)
Keywords: Antarktis; Robert Falcon Scott; Sydpolsekspedisjonen; oppdagelsesreiser

Belåtna svenskar i Antarktis - Lundin, Kjell (Pemmikan : en hårdkokt historia, 2015)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ernæring; mat

"Toffe karer spiser pemmikan" - Lundin, Kjell (Pemmikan : en hårdkokt historia, 2015)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ernæring; mat

Leadership lessons from the race to the South Pole : why Amundsen lived and Scott died - O'Connell, Fergus (Praeger, 2015)
A project management expert identifies methods for running any project successfully based on lessons learned from the exploits of two storied explorers.
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser

Seismic signals from large, tabular icebergs drifting along the Dronning Maud Land coast, Antarctica, and their significance for iceberg monitoring - Pirli, Myrto; Matsuoka, Kenichi; Schweitzer, Johannes; Moholdt, Geir (Journal of Glaciology, 2015)
In this study, we analyze a large dataset of seismic signals, recorded by station TROLL in Dronning Maud Land, Antarctica. The signals, recorded in April–December 2012, came from sources near the edge of the ice shelves, at distances of 230–500 km from TROLL. The sources, which moved westward with time, could be associated with four large, tabular icebergs, drifting between 15° E and 8° W. Combining the seismological data with information from satellite remote sensing, we find that one-third of the signals can be attributed to individual icebergs. The trajectories of three of the associated icebergs are known through iceberg-tracking databases, whereas the fourth, a fragment of one of the other three, is untracked, and only scarce information is available from satellite imagery. The observed seismic signals exhibit a wide variety of frequency characteristics, from unstructured episodes to occurrences of iceberg harmonic tremor. Although we are not able to determine the exact cause of the signals, we classify them into five classes on a phenomenological basis. This study demonstrates the potential of regional seismic networks for iceberg monitoring as supplementary resources to information obtained with remote-sensing technologies.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; isfjell; teknologi

Lateral extrusion at the Eastern margin of the East African-Antarctic Orogen in Dronning Maud Land - Ruppel, Antonia; Läufer, Andreas; Jacobs, Joachim; Elburg, M; Krohne, N; Eagles, Graeme; Mieth, Matthias; Jokat, Wilfried; Damaske, Detlef; Lisker, Frank ([German Society for Polar Research], 2015)
The geology of Sør Rondane has been the focus of intense research and occupies a key position for reconstructing the late Neoproterozoic to early Paleozoic geodynamic evolution in eastern Dronning Maud Land (DML). Sør Rondane appears to be located close to the supposed intersection of the East African-Antarctic Orogen (EAAO) and the Kuunga Orogen. The western part of Sør Rondane is subdivided in two distinct terranes. The amphibolite to granulite-facies NE terrane is mainly composed of metasupracrustal rocks, with detrital zircon ages in part younger than 750 Ma, deposited on older basement of unknown, possibly Rayner-type, crust (Shiraishi et al., 2008). Metamorphism has been dated by U-Pb on zircon at ca. 640-600 Ma and amphibolite-facies retrogression dated at ca. 590-530 Ma. The SW terrane is subdivided by the Main Shear Zone (MSZ) into two lithothectonic units, i.e. Pan- African greenschist- to granulite-facies metamorphic rocks with “East African” affinities in the N and a Rayner-age early Neoproterozoic gabbro-tonalite-trondhjemite-granodiorite (GTTG) complex with “Indo-Antarctic” affinities in the S. The GTTG complex has suffered Pan-African greenschist- to lower amphibolite-facies thermal overprint, but also contains large domains with only weak deformation except for its northern margin close to the MSZ. The deformation there is related to high shear strain along this structure. New zircon crystallisation ages of the GTTG cluster around 1000-930 Ma. It is interpreted to have formed along a juvenile oceanic arc, in which the wide age range might indicate a long-lasting accretionary orogen. The MSZ is characterized by a right-lateral sense of movement and high-strain ductile deformation under peak amphibolite-facies conditions. The structure can be traced over a distance of ca. 120 km between Lågkollane in the W and Lunckeryggen in the E and reaches several hundred meters in width. The MSZ cannot be traced further to the W where it seems to terminate at the north-eastern border of the NW-SE oriented prominent magnetically defined SE DML Province. The north-eastern border zone may coincide with a significant dextral shear zone that runs from the Schirmacher Oasis into the region S of Sør Rondane (Schirmacher- Rondane Lineament). The SE DML Province most likely consists of Rayner-age (1000-900 Ma) crust with evidence of intense Pan-African reworking indicated by new geochronological data and was part of a large Tonian Oceanic Arc Super Terrane (TOAST). The continuation of the MSZ into eastern Sør Rondane and beyond is not clear either, since it appears to terminate at a N-S oriented region with low magnetic signatures (central Sør Rondane corridor) that is possibly related to extensional tectonics. Crosscutting relationships with dated magmatic rocks bracket the activity of the MSZ between Latest Ediacaran to Cambrian times (c. 560- 530 Ma). Based on new combined aeromagnetic and structural results from a four-seasons survey of the greater Sør Rondane region, we propose that the crustal structural architecture of eastern DML and is strongly influenced by N-directed (with Africa/Antarctica restored to its original position in Gondwana) lateral extrusion of the EAAO. This process was likely driven by the combination of (i) indentation of the SE DML block towards the conjugate stable Kalahari- Grunehogna cratonic foreland, (ii) extensional collapse of the previously (c. 580-550 Ma) thickened and gravitational instable crust of central DML, and (iii) large-scale tectonic escape of crustal blocks in eastern DML along major shear zones such as the Schirmacher Rondane Lineament and MSZ towards an unconstrained yet unknown region at a lateral position of the EAAO.
Keywords: Dronning Maud Land; geologi

Norske interesser og politikk for Bouvetøya - [s.n.] (Melding til Stortinget, 2015)
Helt siden Bouvetøya ble norsk biland i 1930 har denne øya langt sør i Atlanterhavet vært del av vår polare identitet og historie. Gjennom tidene har øya likevel ikke vært gjenstand for stor oppmerksomhet. Siden 1930 har det heller ikke vært gitt noen samlet omtale til Stortinget av forhold som angår forvaltningen av dette området. Regjeringen mener det nå er tid for å gjøre Bouvetøya bedre kjent gjennom en melding til Stortinget. Denne meldingen har derfor som mål å beskrive Bouvetøya, og gi en bred fremstilling av ulike forhold når det gjelder rettslige rammebetingelser, forvaltning og aktivitet på øya og i havområdene rundt. Regjeringen fremmer også en melding til Stortinget som omhandler norske interesser og politikk i Antarktis, herunder de norske bilandene Dronning Maud Land og Peter I Øy, heretter omtalt som Antarktismeldingen. 1 Tradisjonelt har de tre bilandene Bouvetøya, Dronning Maud Land og Peter I Øy vært omtalt sammen. Bouvetøya ligger nord for Antarktistraktatens virkeområde, og er ubestridt norsk territorium. Regjeringen har derfor funnet det hensiktsmessig å legge frem en egen melding om norske interesser og politikk for Bouvetøya. Spørsmål som gjelder Bouvetøya håndteres som en integrert del av norsk politikk. Dette inne- bærer å gjøre norsk lovgivning gjeldende for øya i den grad det er hensiktsmessig, og å sørge for at lovgrunnlaget er tilpasset behovene. I denne meldingen om Bouvetøya beskrives intern lovgivning så vel som det folkerettslige rammeverket, og ret- tighetene og pliktene som følger av dette, herunder retten til naturressurser og plikten til å ta vare på miljøet. Det gis en egen omtale av de stats- rettslige sidene ved øya, og av at det vil bli vurdert om disse og andre forhold bør reguleres i en egen lov.
Keywords: Bouvetøya; forvaltning; lovgivning; overvåking; politikk; økonomi

Review of the low-temperature thermochronological data from the Dronning Maud Land Mountains, East Antarctica - Sirevaag, Hallgeir; Jacobs, Joachim; Ksienzyk, Anna Katharina; Dunkl, István (Norsk Geologisk Forening (NGF), 2015)
The paleo-topography of East Antarctica is highly relevant for the development of the East Antarctic ice-sheet. This ice-sheet originated probably as small ice caps and in the elevated areas of the cratons in East Antarctica around the Eocene/Oligocene boundary. East Antarctica contains three mountain ranges: the latitudinal Dronning Maud Land Mountains (DML), the longitudinal Transantarctic Mountains (TAM) and the sub-glacial Gamburtsev Mountains (GM). The 1500 km long, coast-parallel Dronning Maud Land Mountains probably resulted in a significant amount of precipitation prior to the initiation of the 34 Ma glaciation history of East Antarctica. Thus, the paleo-topography should be used as an important input parameter for the glaciation history.
Keywords: Dronning Maud Land; geologi

The significance of petroleum for the South Pole expeditions 1910-1912 - Skarung, Per (The Fram Museum, 2015)
"Inclement weather and lack of fuel was the cause of their deaths".
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; polarhistorie

Polare strøk. Skippere og fangstfolk. Den nye tid - Aasheim, Stein P. (Norske eventyrere, 2014)
Keywords: Antarktis; Bernt Balchen; Carl Anton Larsen; Carsten Borchgrevink; Nordmenn; Tryggve Gran; geografi; historie; oppdagelsesreiser; polarekspedisjoner

Hiihtovaellus etelänavalle : eräretki Roald Amundsenin jäljissä - Aasheim, Stein P; Paarma, Susanna (Gummerus, 2014)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

[Bir kəşfiyyatçı kimi həyatım] - Amundsen, Roald (Alatoran, 2014)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Inspeksjonsordningen under Antarktistraktaten - Bech, Jon (Polarboken, 2014)
Keywords: Antarktis; jus; politikk

Kanten av isødet - Blackadder, Jesse; Berg, Ellen Karine (Juritzen, 2014)
Roman om tre kvinner fra Sandefjord og kampen om å komme først til Antarktis. Sandefjord 1930. Ingrid er gift med byens hvalkonge, Lars Christiansen. Hun har drømt om å reise til Antarktis siden hun var barn, og nå har ektemannen lovet å ta henne med på en av hvalbåtene. Betingelsen er at hun har med seg en kvinnelig ledsager, og den deprimerte enken Mathilde blir motvillig rekruttert. Samtidig sitter Lillemor Rachlew i London og ønsker mest av alt å bli første kvinne i Antarktis. Hun får høre om reisen til Ingrid, og får lurt seg med på samme båt rett før den forlater Cape Town. Kappløpet mot et livsfarlig isøde er i gang, og reisen vil bli skjebnesvanger for alle de tre kvinnene. Denne fascinerende romanen er basert på virkelige hendelser. Vi blir tatt med til 1930-årenes Sandefjord, til hvalfangstindustriens gullalder, og blir kjent med tre kvinner som kjempet ikke bare for sin selvstendighet, men også for sin plass i historien.
Keywords: Antarktis; Nordmenn; ekspedisjoner; fortellinger; kvinner; oppdagelsesreiser

Transition of flow regime along a marine-terminating outlet glacier in East Antarctica - Callens, Denis; Matsuoka, Kenichi; Steinhage, Daniel; Smith, Benjamin; Witrant, E; Pattyn, Frank (The Cryosphere, 2014)
We present results of a multi-methodological approach to characterize the flow regime of West Ragnhild Glacier, the widest glacier in Dronning Maud Land, Antarctica. A new airborne radar survey points to substantially thicker ice (>2000 m) than previously thought. With a discharge estimate of 13–14 Gt yr−1, West Ragnhild Glacier thus becomes of the three major outlet glaciers in Dronning Maud Land. Its bed topography is distinct between the upstream and downstream section: in the downstream section (<65 km upstream of the grounding line), the glacier overlies a wide and flat basin well below the sea level, while the upstream region is more mountainous. Spectral analysis of the bed topography also reveals this clear contrast and suggests that the downstream area is sediment covered. Furthermore, bed-returned power varies by 30 dB within 20 km near the bed flatness transition, suggesting that the water content at bed/ice interface increases over a short distance downstream, hence pointing to water-rich sediment. Ice flow speed observed in the downstream part of the glacier (~250 m yr−1) can only be explained through very low basal friction, leading to a substantial amount of basal sliding in the downstream 65 km of the glacier. All the above lines of evidence (sediment bed, wetness and basal motion) and the relatively flat grounding zone give the potential for West Ragnhild Glacier to be more sensitive to external forcing compared to other major outlet glaciers in this region, which are more stable due to their bed geometry (e.g. Shirase Glacier).
Keywords: Dronning Maud Land; glasiologi

Commonness and rarity in the marine biosphere - Connolly, Sean R; MacNeil, M Aaron; Caley, M Julian; Knowlton, Nancy; Cripps, Ed; Hisano, Mizue; Thibaut, Loïc M; Bhattacharya, Bhaskar D; Benedetti-Cecchi, Lisandro; Brainard, Russell E; Brandt, Angelika; Bulleri, Fabio; et al. (Proceedings of the National Academy of Sciences, 2014)
Tests of biodiversity theory have been controversial partly because alternative formulations of the same theory seemingly yield different conclusions. This has been a particular challenge for neutral theory, which has dominated tests of biodiversity theory over the last decade. Neutral theory attributes differences in species abundances to chance variation in individuals’ fates, rather than differences in species traits. By identifying common features of different neutral models, we conduct a uniquely robust test of neutral theory across a global dataset of marine assemblages. Consistently, abundances vary more among species than neutral theory predicts, challenging the hypothesis that community dynamics are approximately neutral, and implicating species differences as a key driver of community structure in nature.Explaining patterns of commonness and rarity is fundamental for understanding and managing biodiversity. Consequently, a key test of biodiversity theory has been how well ecological models reproduce empirical distributions of species abundances. However, ecological models with very different assumptions can predict similar species abundance distributions, whereas models with similar assumptions may generate very different predictions. This complicates inferring processes driving community structure from model fits to data. Here, we use an approximation that captures common features of “neutral” biodiversity models—which assume ecological equivalence of species—to test whether neutrality is consistent with patterns of commonness and rarity in the marine biosphere. We do this by analyzing 1,185 species abundance distributions from 14 marine ecosystems ranging from intertidal habitats to abyssal depths, and from the tropics to polar regions. Neutrality performs substantially worse than a classical nonneutral alternative: empirical data consistently show greater heterogeneity of species abundances than expected under neutrality. Poor performance of neutral theory is driven by its consistent inability to capture the dominance of the communities’ most-abundant species. Previous tests showing poor performance of a neutral model for a particular system often have been followed by controversy about whether an alternative formulation of neutral theory could explain the data after all. However, our approach focuses on common features of neutral models, revealing discrepancies with a broad range of empirical abundance distributions. These findings highlight the need for biodiversity theory in which ecological differences among species, such as niche differences and demographic trade-offs, play a central role.
Keywords: Sørishavet; biodiversitet; biologi; marin økologi; marine økosystemer; polarområdene; zoologi

Annual cycle of Antarctic Baseline Aerosol: A Benchmark for Natural Aerosol Processes - Fiebig, Markus; Hirdman, David; Lunder, Chris R; Ogren, John A; Solberg, Sverre; Thompson, Rona L; Stohl, Andreas (2014)
An ongoing challenge in attributing anthropogenic climate change is to distinguish anthropogenic and natural changes of atmospheric composition, e.g. concerning atmospheric aerosol and its climate effects. Aerosol properties measured at pristine locations, to the extend they still exist, can serve as a climate model benchmark for verifying the representation of natural aerosol processes in the model.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; klimaendringer; klimamodeller

Commercial fishing vessel as research vessels in the Antarctic – Requirements and solutions exemplified with a new vessel - Godø, Olav; Reiss, Christian; Siegel, V; Watkins, Jonathan (CCAMLR science journal of the Scientific Committee and the Commission for the Conservation of Antarctic Marine Living Resources, 2014)
Keywords: Antarktis; fiskefartøy; forskning; forskningsfartøy; klimaendringer; oseanografi; økosystem

Comparative study on PCDD/F pollution in soil from the Antarctic, Arctic and Tibetan Plateau - Jia, Shenglan; Wang, Qiang; Li, Li; Fang, Xuekun; Shi, Yehong; Xu, Weiguang; Hu, Jianxin (Science of the Total Environment, 2014)
The concentrations of polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) in 35 soil samples collected from Fildes Peninsula in the Antarctic, Ny-Ålesund in the Arctic, and Zhangmu-Nyalam in the Tibetan Plateau were reported in this study. A comparison of the total concentration and TEQ of PCDD/Fs at the Three Poles was conducted. Both the total concentration and TEQ of PCDD/Fs demonstrates a decreasing trend in the order of Zhangmu-Nyalam (mean: 26.22 pg/g, 0.37 pg I-TEQ/g)>Ny-Ålesund (mean: 9.97 pg/g, 0.33 pg I-TEQ/g)>Fildes Peninsula (mean: 2.18 pg/g, 0.015 pg I-TEQ/g) (p<0.05). In all samples, the congener and homologue profiles dominated with higher (seven and eight) chlorinated PCDD/Fs (more than 85% of the total mass percentage of PCDD/Fs) at the Three Poles. Finally, a FLEXPART backward simulation was used to preliminarily identify the potential local and regional anthropogenic sources of PCDD/Fs. The results imply that the air masses passing over surrounding regions with significant PCDD/F emissions might contribute to the occurrence of PCDD/Fs in both the Arctic and Tibetan Plateau.
Keywords: Antarktis; menneskelig påvirkning; miljøgifter; miljøovervåking; polarområdene

The Third Expedition, 1910-1912: Antarctica and the Southern Ocean - Johnson, Charles W (Ice ship : the epic voyages of the polar adventurer Fram, 2014)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Fjerning av reinsdyr på Sør-Georgia: nok et avsluttet kapittel i norsk hvalfangsthistorie - Kilander, Carl Erik (Polarboken, 2014)
Keywords: Sørishavet; zoologi; økologi

Et besøk på Bettyfjellet - Kristensen, Monica; McIntyre, Neil (Polarboken, 2014)
Keywords: Antarktis; ekspedisjoner; historie

High variability of climate and surface mass balance induced by Antarctic ice rises - Lenaerts, Jan T M; Joel, Brown.; Van Den Broeke, Michiel R; Matsuoka, Kenichi; Drews, Reinhard; Callens, Denis; Philippe, Morgane; Gorodetskaya, Irina V; Van Meijgaard, Erik; Reijmer, Carleen H; Pattyn, Frank; Van Lipzig, Nicole P M (Journal of Glaciology, 2014)
Ice rises play key roles in buttressing the neighbouring ice shelves and potentially provide palaeoclimate proxies from ice cores drilled near their divides. Little is known, however, about their influence on local climate and surface mass balance (SMB). Here we combine 12 years (2001–12) of regional atmospheric climate model (RACMO2) output at high horizontal resolution (5.5 km) with recent observations from weather stations, ground-penetrating radar and firn cores in coastal Dronning Maud Land, East Antarctica, to describe climate and SMB variations around ice rises. We demonstrate strong spatial variability of climate and SMB in the vicinity of ice rises, in contrast to flat ice shelves, where they are relatively homogeneous. Despite their higher elevation, ice rises are characterized by higher winter temperatures compared with the flat ice shelf. Ice rises strongly influence SMB patterns, mainly through orographic uplift of moist air on the upwind slopes. Besides precipitation, drifting snow contributes significantly to the ice-rise SMB. The findings reported here may aid in selecting a representative location for ice coring on ice rises, and allow better constraint of local ice-rise as well as regional ice-shelf mass balance.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima

Post-breeding at-sea movements of three central-place foragers in relation to submesoscale fronts in the Southern Ocean around Bouvetøya - Lowther, Andrew D; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg J G; Kovacs, Kit M (Antarctic Science, 2014)
Keywords: Bouvetøya; oseanografi; pelsseler; pingviner; satellitt; telemetri

Å filme de dypfrosne hemmelighetene til en aktiv vulkan - Roberts, Jason (Polarboken, 2014)
Keywords: Antarktis; film; geofysikk; vulkaner

Norge i Antarktis - Rognhaug, Magnus Hovind (red.) (Norsk Polarinstitutt, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Sørishavet; forskning; miljøvern; polarforskning; politikk

Future challenges in environmental management of National Antarctic Programs - Sánchez, Rodolfo Andrés; Njåstad, Birgit (Antarctic futures : human engagement with the Antarctic environment, 2014)
Keywords: Antarktis; miljøvern

Hvalfangerkirken i Grytviken 100 år - Tokstad, Kjell (Polarboken, 2014)
Keywords: Sørishavet; bygninger; historie

Thick-shelled, grazer-protected diatoms decouple ocean carbon and silicon cycles in the iron-limited Antarctic Circumpolar Current - Assmy, Philipp; Smetacek, Victor; Montresor, Marina; Klaas, Christine; Henjes, Joachim; Strass, Volker; Arrieta, Jesus M; Bathmann, Ulrich; Berg, Gry Mine; Breitbarth, Eike; Cisewski, Boris; Friedrichs, Lars; et al. (Proceedings of the National Academy of Sciences, 2013)
Diatoméer – alger med skall av silisium, som er helt avhengige av næringsstoffet silikat – dominerer fytoplankton oppblomstringer og spiller en nøkkelrolle i havets økosystemer og i global karbonsyklus. Vi viser hvordan forskjeller i økologiske karakteristikker av dominerende arter i Sørishavet, som ble observert under det in situ europeiske jerngjødslings eksperimentet (European Iron Fertilization Experiment - EIFEX), kan påvirke karbon og silisium syklusene i havet. Vi argumenterer for at økologien til tykkskallete diatomé arter, som er selektert for av sterk beiting fra kopepoder, tar opp silikat fremfor andre næringsstoffer i det dype Sørishavet og underliggende sedimenter. Fordi Sørishavet er en viktig sentral for oseanisk fordeling av næringsstoffer, selektivt opptak av silikat i dette havområdet begrenser oppblomstringene av diatoméer i andre deler av verdenshavene, noe som potensielt får konsekvenser for biotisk opptak av karbon i hele verdens havområder.
Keywords: Sørishavet; marinbiologi; oseanografi; plankton; økosystem

Antarktis-isen: større og dypere - Bjermeland, Monica (Klima: norsk magasin for klimaforskning, 2013)
De siste tiårene har isen i Antarktis økt litt i utbredelse. Men ikke fordi det er blitt kaldere der.
Keywords: Antarktis; Sørishavet; glasiologi; havis; is; klima

Women, whales and Antarctica - Blackadder, Jesse (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Antarktis; første landgang; historie; kvinner; oppdagelsesreiser

Did a Dutch company kill whales with tax payers' money after world war II? - Bruijn, Jaap R; Schokkenbroek, Joost C A (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; pelagisk; sjøfolk

Genetic characterization and life cycle of the diatom Fragilariopsis kerguelensis - Fuchs, Nike; Scalco, Eleonora; Kooistra, Wiebe; Assmy, Philipp; Montresor, Marina (European Journal of Phycology, 2013)
Diatoméen Fragilariopsis kerguelensis fra Sørishavet spiller en nøkkelrolle i marin silisium syklus fordi restene av celleveggene synker til havbunnen rundt Antarktis, hvor de bygger opp de største depotene av biologisk generert silisium i verden. Tomme skall av diatomeer har også blitt brukt som indikatorer/proksier for produksjonsregimer i geologisk fortid av mikro-paleontologer. For å bedre kunne beskrive og forstå biologien av denne arten fra Sørishavet har vi adressert dens genetiske identitet ved hjelp av molekylære markører, og for første gang vært i stand til å anslå kjønn til denne arten. Dette har ført til at vi har vært i stand til å kjøre et stort antall vellykkede parringseksperimenter. Vi har vært i stand til å avdekke det intrikate parringssystemet og livssyklus karakteristikker til F. kerguelensis og demonstrere at vi kun har å gjøre med én biologisk art. En bedre forståelse av livssyklus til F. kerguelensis burde hjelpe for tolkning av geologiske tidsserier for denne arten og belyse rollen miljøfaktorer kan ha for å regulere populasjoner av arten.
Keywords: Sørishavet; genetikk; marinbiologi; plankton

Oral sources at the whaling museum: from speech to text and exhibition - Garmel, Hanne (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Nordmenn; Sørishavet; erindringer; hvalfangst; museer; pelagisk

Tre kilder til smelting av Fimbulisen - Hattermann, Tore; Nøst, Ole A; Smedsrud, Lars H (Klima: norsk magasin for klimaforskning, 2013)
Soloppvarmet overflatevann er en sentral varmekilde som bidrar til smelting av isbremmen Fimbulisen i Dronning Maud Land.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima

Neoproterozoic/Lower Palaeozoic geodynamic evolution of Dronning Maud Land: integrating geology and geophysics - Jacobs, Joachim; Läufer, Andreas; Clark, Chris; Kleinhanns, Ilka; Elburg, Marlina; Ruppel, Antonia; Estrada, Solveig; Damaske, Detlef; Jokat, Wilfried; Riedel, Sven; Lucka, Nicole (Changing polar regions : 25th International Congress on Polar Research ; March 17-22, 2013, Hamburg, Germany, 2013)
East Antarctica probably formed by amalgamation of a number of cratons along distinct Ediacaran mobile belts, including the ca. 600-500 Ma East African-Antarctic Orogen (EAAO) that dissects Dronning Maud Land (DML). New field-work during the international expeditions Geodynamic Evolution of East Antarctica (GEA) I + II in the austral summers 2010/11 and 2011/12, and first geochronological results from eastern DML reveal a complex tectonic architecture across the belt. In western DML, the EAAO reworks older Mesoproterozoic crust of the Maud Belt; the westernmost boundary of the mobile belt is characterized by a major dextral transpressional shear zone. In central DML, a major magnetic anomaly, the Forster anomaly, was interpreted as a cryptic suture of the EAAO (Riedel et al. 2012). The area where the Forster anomaly crosses the DML mountains is poorly investigated so far, but appears to coincide with a major strike slip shear zone in the southern Kurze Mts. and the occurrence of major Ediacaran granulite bodies. East of the Forster anomaly, the magnetic anomaly pattern changes significantly and typical Maud type crust is not present any longer. GEA II targeted a range of nunataks between Sør Rondane and central DML that had never been visited previously (from Blåklettane and Bergekongen in the E to Urna and Sørsteinen in the W). These nunataks are dominated by medium- to high-grade metasedimentary and metavolcanic rocks of possibly Neoproterozoic age, including abundant marble and graphite schists. Sør Rondane in eastern DML, is dominated by two distinct blocks separated by the dextral Main Shear Zone. The northwestern block is still part of the eastern EAAO, where new SHRIMP zircon data from metamorphic rims provide ages of ca. 560 Ma. The southeastern block is made up of a TTG terrane, which provides four new SHRIMP zircon dates between 990-980 Ma, interpreted as igneous crystallization ages (oceanic arc). The TTG terrane shows limited tectonic overprint and is likely the southeastern foreland of the EAAO. Close to the contact of the two blocks grey geisses and augen-gneisses gave zircon crystallization ages of ca. 750 Ma, ages which were previously unknown from the EAAO. The Forster anomaly therefore separates distinctly different parts of the EAAO: a) a reworked, mainly Grenville-age crust to the W (the overprinted margin of the Kalahari Craton) and b) a part of the orogen dominated by Neoproterozoic accretionary tectonics to the E. This difference is also reflected in the geochemistry of voluminous late-tectonics granitoids across the belt.
Keywords: Dronning Maud Land; geofysikk; geologi

Proterozoic Evolution of Central Dronning Maud Land (East Antarctica) from Rodinia to Gondwana - Jacobs, Joachim; Läufer, Andreas; Clark, Chris; Kleinhanns, Ilka; Elburg, Marlina; Ruppel, Antonia; Estrada, Solveig; Damaske, Detlef; Jokat, Wilfried; Riedel, Sven; Lucka, Nicole (Geochemical Society and of the European Association of Geochemistry, 2013)
Central Dronning Maud Land (CDML) in East Antarctica is an important region for understanding Rodinia and Gondwana supercontinent cycles. Zircon U-Pb dating and Hf-O isotopic data revealed by extensive sampling across CDML provide constraints on the timing and source of main magmatism and new insights into the crustal composition and evolution. SIMS zircon U-Pb ages indicate multi-stage magmatic activities from Mesoproterozoic to Cambrian times at 1160-1130 Ma, 1115-1100 Ma, 1090-1070 Ma, 780-750 Ma, 645-600 Ma and 530-485 Ma, as well as Mesoproterozoic metamorphism at 1085-1050 Ma recorded by zircon rims. This region was subjected a large-scale and long-lasting high-grade metamorphism during 600-500 Ma. Most 1160-1080 Ma granitic rocks exhibit εHf (t) values ranging from +5 and +8 and δ18O slightly higher than mantle value (6-7 ‰), indicating a main derivation from juvenile crust. The involvement of Paleoproterozoic continental materials, which were most likely from adjacent Kalahari Craton, is attested by minor samples with negative to neutral εHf (t) and significantly elevated δ18O values (8-10 ‰). The late Neoproterozoic (750-600 Ma) rocks, including anorthosite, charnockite and granite, display an evolved Hf isotopic composition and high δ18O values (7.5-9 ‰), suggesting a significant addition of crust-derived materials into the source. The data imply that in CDML, late Mesoproterozoic (Grenville-age) magmatism during the assembly of Rodinia is dominated by the addition of new crust with subordinate reworking of ancient crust. Subsequent subduction process associated with the break-up of Rodinia and assembly of Gondwana largely witnessed recycling of previous continental components. Combined with whole-rock geochemistry, it is speculated that the accretionary process along the Maud margin of Kalahari Craton lasted from the Mesoproterozoic, across the late Tonian (750 Ma) until Ediacaran to suture west and east Gondwana blocks.
Keywords: Dronning Maud Land; geokjemi; geologi

Cetus soveticus: exotic and collective cultures of Soviet whaling within the 1960s - Jones, Ryan Tucker (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Nordmenn; Sørishavet; hvalfangst; pelagisk

Bouvetøya : a cultural history of an isolated landmass - Mathews, Freddy Dewe (Freddy Dewe Mathews, 2013)
Keywords: Bouvetøya; historie; kultur

Whaling, lobbying and politics - Ringstad, Jan Erik (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalindustri; pelagisk; politikk

The friend who outstayed his welcome? Johan Hjort and the difficulties of bringing science to bear upon whaling - Roberts, Peder (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Sørishavet; fiskeripolitikk; forskning; hvalbestanden; hvalfangst; pelagisk

De flytende kokeriene : telegraf - Willem Barendsz (II) - Røsset, Geir; Rae, Jim; Basberg, Bjørn L (Novus, 2013)
Denne boken viser med tekst og bilder utviklingen av hvalkokeriene fra de første dampskipene ble ombygget like etter 1900. Den viser hvordan det i mange år fortsatt også ble brukt seilskip, og hvordan skipene gradvis ble større og bedre utrustet. Gradvis ble de til «flytende fabrikker».
Keywords: Sørishavet; fangstfartøyer; historie; hvalbåter; hvalfangstindustri; hvalfangstskip; hvalindustri; hvalkokerier; pelagisk

Sydpolfarerne Per Savio og Ole Must : liv i grenseland - Sandholm, Unni Aas (Temahefter Aas Sandholm, 2013)
Keywords: Antarktis; Southern Cross; Sydpolen; ekspedisjonen; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

Tryggve Gran : is, luft og krig - Simonsen, Anne Hege (Cappelen Damm, 2013)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; oppdagelsesreiser; polarområdene

Da Norge annekterte Bouvetøya - Skagestad, Odd Gunnar (Historie (Bergen), 2013)
Keywords: Bouvetøya; historie; politikk

Hvordan Bouvetøya ble norsk - Skagestad, Odd Gunnar (UD-posten: husorgan for utenrikstjenesten, 2013)
Keywords: Bouvetøya; historie; politikk

Vår sydligste provins: Dronning Maud Land 75 år - Skagestad, Odd Gunnar (Historie (Bergen), 2013)
Keywords: Dronning Maud Land; historie; politikk

I Roald Amundsens skispor : kappløpet til Sørpolen - 100 år etter - Aasheim, Stein P (Cappelen Damm, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

Den japanske antarktisekspedisjonen i 1912 - Barr, Susan (Polarboken, 2012)
Keywords: Antarktis; ekspedisjoner; historie

The state of the poles : climate lessons from the International Polar Year - Bjørnæs, Christian; Prestrud, Pål (Unipub, 2012)
Keywords: Antarktis; klimaendringer; polarforskning; polarområdene

Roald Amundsen: Forsker eller grobian? - Blix, Arnoldus Schytte (Nordisk tidskrift för vetenskap, konst och industri, 2012)
Roald Amundsens (1872-1928) liv og bedrifter er fremstilt i en rekke biografier, men det er oppdageren og eventyreren som blir tillagt mest vekt, mens vitenskapsmannen og forskeren tidvis underkjennes. Professor i arktisk biologi ved Universitetet i Tromsø, Arnoldus Schytte Blix, er kritisk til mye av det biografiske arbeidet som er gjort, og mener det er et åpent spørsmål om kontorhistorikere og journalister har noen reell mulighet til fullt ut å forstå Roald Amundsens situasjon og reaksjoner. Artikkelen er basert på et foredrag med en rekke illustrasjoner i Det Norske Videnskabs-Akademi, 17. november 2011.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; biografier; oppdagelsesreiser

Til Sydpolen - 100 år etter - Johansen, Asle T; Grindhaug, Gaute; Berg, Agnar (Fri flyt, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

The South Pole expedition of Roald Amundsen: how did he prepare for the expedition and what do his crewmembers' diaries tell us about it? / Geir O. Kløver. - Kløver, Geir Olav (Nimrod : the Journal of the Ernest Shackleton Autumn School, 2012)
Describes Amundsen's experience on de Gerlache's 1897-99 Belgica Antarctic expedition, scientific interests, lessons learned on his 1903-06 Gjøa Northwest Passage expedition, and experience on 1910-12 Fram Antarctic expedition. Gives details of crew members on Antarctic expedition with account of their diaries. Author is director of Fram Museum and editor of South Pole diaries of Amundsen and fourteen of his crew members.
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; dagbøker; polarhistorie

Antarctic krill swarm characteristics in the Southeast Atlantic sector of the Southern Ocean - Krafft, Bjørn A.; Skaret, Georg; Knutsen, Tor; Melle, Webjørn; Klevjer, Thor; Søiland, Henrik (Marine ecology. Progress series, 2012)
Knowledge about swarm dynamics and underlying causes is essential to understand the ecology and distribution of Antarctic krill . We collected acoustic data and key environmental data continuously across extensive gradients in the little-studied Southeast Atlantic sector of the Southern Ocean. A total of 4791 krill swarms with swarm descriptors including swarm height and length, packing density, swimming depth and inter-swarm distance were extracted. Through multivariate statistics, swarms were categorized into 4 groups. Group 2 swarms were largest (median length 108 m and thickness 18 m), whereas swarms in both Groups 1 and 4 were on average small, but differed markedly in depth distribution (median: 52 m for Group 1 vs. 133 m for Group 4). There was a strong spatial autocorrelation in the occurrence of swarms, and an autologistic regression model found no prediction of swarm occurrence from environmental variables for any of the Groups 1, 2 or 4. Probability of occurrence of Group 3 swarms, however, increased with increasing depth and temperature. Group 3 was the most distinctive swarm group with an order of magnitude higher packing density (median: 226 ind. m ) than swarms from any of the other groups and about twice the distance to nearest neighbor swarm (median: 493 m). The majority of the krill were present in Group 3 swarms, and the absence of association with hydrographic or topographic concentrating mechanisms strongly suggests that these swarms aggregate through their own locomotion, possibly associated with migration.
Keywords: Bouvetøya; Sørishavet; datainnsamling; ekkolodd; krill; marin biologi; plankton; økologi

Antarktis - Langerud, Per Jan (Klima, is og forskerfeil, 2012)
Keywords: Antarktis; klimaendringer; klimaforskning

Radar characterization of the basal interface across the grounding zone of an ice-rise promontory in East Antarctica - Matsuoka, Kenichi; Pattyn, Frank; Callens, Denis; Conway, Howard (Annals of Glaciology, 2012)
Radar power returned from the basal interface along a 42 km long profile over an ice-rise promontory and the adjacent Roi Baudouin ice shelf, Dronning Maud Land, East Antarctica, is analyzed to infer spatial variations in basal reflectivity and hence the basal environment. Extracting basal reflectivity from basal returned power requires an englacial attenuation model. We estimate attenuation in two ways: (1) using a temperature-dependent model with input from thermomechanical ice-flow models; and (2) using a radar method that linearly approximates the geometrically corrected returned power with ice thickness. The two methods give different results. We argue that attenuation calculated using a modeled temperature profile is more robust than the widely used radar method, especially in locations where depth-averaged attenuation varies spatially or where the patterns of basal reflectivity correlate with the patterns of the ice thickness.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

The Mapping of Antarctica - Pedersen, Jakob Søndergård; Curtis, Philip (The Map House, 2012)
Keywords: Antarktis; ekspedisjoner; kart; kartlegging; kartografi; oppdagelsesreiser

Cecilie Skog. Liv Arnesen. Monica Kristensen - Sandberg, Sigri (Polarheltinner : Cecilie Skog, Liv Arnesen, Monica Kristensen, Christiane Ritter, Wanny Woldstad, Ellen Dorthea Nøis, Hanna Resvoll-Holmsen, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjoner; biografier; friluftsliv; kvinner; polarekspedisjoner; polarhistorie

Extent of low-accumulation 'wind glaze' areas on the East Antarctic plateau: implications for continental ice mass balance - Scambos, Ted A; Frezzotti, Massimo; Haran, T; Bohlander, J; Lenaerts, Jan T M; Van Den Broeke, M R; Jezek, K; Long, D; Urbini, S; Farness, K; Neumann., T; Albert, M; et al. (Journal of Glaciology, 2012)
Persistent katabatic winds form widely distributed localized areas of near-zero net surface accumulation on the East Antarctic ice sheet (EAIS) plateau. These areas have been called 'glaze' surfaces due to their polished appearance. They are typically 2-200 km2 in area and are found on leeward slopes of ice-sheet undulations and megadunes. Adjacent, leeward high-accumulation regions (isolated dunes) are generally smaller and do not compensate for the local low in surface mass balance (SMB). We use a combination of satellite remote sensing and field-gathered datasets to map the extent of wind glaze in the EAIS above 1500 m elevation. Mapping criteria are derived from distinctive surface and subsurface characteristics of glaze areas resulting from many years of intense annual temperature cycling without significant burial. Our results show that 11.2 ± 1.7%, or 950 ± 143 × 103km2, of the EAIS above 1500 m is wind glaze. Studies of SMB interpolate values across glaze regions, leading to overestimates of net mass input. Using our derived wind-glaze extent, we estimate this excess in three recent models of Antarctic SMB at 46-82 Gt. The lowest-input model appears to best match the mean in regions of extensive wind glaze.
Keywords: Antarktis; glasiologi

Nansen-Amundsen-året 2011 - Schreuder, Janne (ed.); Jaklin, Gunn Sissel (ed.) (Norsk Polarinstitutt, 2012)
Keywords: Antarktis; Roald Amundsen; jubileer; polarområdene

Sydpolen eller Sørpolen? - Skagestad, Odd Gunnar (Ordet: kvartalsskrift for riksmålsbevegelsen, 2012)
Keywords: Antarktis; språk; stedsnavn

Virvler øker smeltingen - Smedsrud, Lars H; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Kovacs, Kit M; Nøst, Ole A (Klima: norsk magasin for klimaforskning, 2012)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima; oseanografi

Of reindeer, ponies and automobiles : Roald Amundsen and the Norwegian bid for the South Pole - Turney, Chris (1912 : the year the world discovered Antarctica, 2012)
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Veivisere under sydkorset - Walsøe, Jan Oskar (Sophie Borchgrevink Nordrum og Ivar O. Nordrum, 2012)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; kartlegging; oppdagelsesreiser; polarområdene

Impact of increasing Antarctic ice-shelf melting on Southern Ocean hydrography - Wang, Caixin; Wang, Keguang (Journal of Glaciology, 2012)
Southern Ocean hydrography has undergone substantial changes in recent decades, concurrent with an increase in the rate of Antarctic ice-shelf melting (AISM). We investigate the impact of increasing AISM on hydrography through a twin numerical experiment, with and without AISM, using a global coupled sea-ice/ocean climate model. The difference between these simulations gives a qualitative understanding of the impact of increasing AISM on hydrography. It is found that increasing AISM tends to freshen the surface water, warm the intermediate and deep waters, and freshen and warm the bottom water in the Southern Ocean. Such effects are consistent with the recent observed trends, suggesting that increasing AISM is likely a significant contributor to the changes in the Southern Ocean. Our analyses indicate potential positive feedback between hydrography and AISM that would amplify the effect on both Southern Ocean hydrography and Antarctic ice-shelf loss caused by external factors such as changing Southern Hemisphere winds.
Keywords: Sørishavet; glasiologi; hydrografi

Cold recall: Roald Amundsen's reflections from the South Pole - Amundsen, Roald; Kløver, Geir O (Fram Museum, 2011)
Keywords: Antarktis; ekspedisjoner; historie

Polar settlements : location, techniques and conservation - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2011)
Keywords: Antarktis; hvalfangststasjoner; kulturminnevern; polarforskning; polarområdene; turisme

Sydpolsekspedisjonen 1910-1912 - Bjaaland, Olav (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

The ANTOSTRAT Legacy: Science Collaboration and International Transparency in Potential Marine Mineral Resource Exploitation of Antarctica - Cooper, Alan; Barker, Peter; Barrett, Peter; Behrendt, John; Brancolini, Giuliano; Childs, Jonathan; Escutia, Carlota; Jokat, Wilfried; Kristoffersen, Yngve; Leitchenkov, German; Stagg, Howard; Tanahashi, Manabu; et al. (Science Diplomacy: Antarctica, Science, and the Governance of International Spaces, 2011)
Keywords: Antarktis; geopolitikk; internasjonal samarbeid; marin geologi; mineraler; ressurser; stratigrafi; tektonikk

Belgica. South Pole. The Heroic Dogs. Darkness and Light. Amundsen and Byrd - Cox, Lynne (South with the sun : Roald Amundsen, his polar explorations, and the quest for discovery, 2011)
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjonen; Sydpolen; oppdagelsesreiser; polarekspedisjoner; sledehunder

Sydpolsekspedisjonen 1910-1912 - Gjertsen, Hjalmar Fredrik (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Hassel, Sverre (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Ecosystem study and krill survey aboard G.O. Sars in Southern Ocean - Iversen, Svein A; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Bouvetøya; Det Internasjonale polaråret 2007; krill; marine økosystemer; plankton; polarforskning

Sydpolsekspedisjonen 1910-1912 - Johansen, Hjalmar (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Das Eis und der Tod : Scott, Amundsen und das Drama am Südpol - Jostmann, Christian (Beck, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Der Wettlauf zum Südpol : das grösste Abenteuer der Geschichte - Knopp, Guido; Sporn, Mario; Schnier, Marten (Bertelsmann, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Seals used as "research assistants" in the polar oceans - Kovacs, Kit M; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr

Bildeberetninger. Mediebegivenheter. Polprospekter - Lund, Harald Østgaard; Berg, Siv Frøydis (Norske polarheltbilder : 1888-1928, 2011)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; fotografi; fotohistorie; kulturhistorie; polarekspedisjoner; polarområdene; polfarere

Race to the end : Scott, Amundsen and the South Pole - MacPhee, Ross D E (The Natural History Museum, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

På hvalfangst, 1955-56 - Mortensen, Mauritz Sundt (Atlantic Press, 2011)
Keywords: Sørishavet; hvalfangst

Sydpolsekspedisjonen 1910-1914 - Nilsen, Thorvald (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; oseanografi; polarområdene

The present location of the tent that Roald Amundsen left behind at the South Pole in December 1911 - Orheim, Olav (Polar Record, 2011)
Determining the present precise location of Amundsen's tent is a function of 1) the precision of Amundsen's navigation in 1911, 2) the flow of ice since then, and 3) the amount of burial by intervening snow fall. These factors are discussed and it is concluded that the best location that can be given for the tent in December 2011 is 89° 58′ 51″ S, 46° 14′ E, and lying 17 m below the present snow surface. The uncertainty in the position is 0.3 km, and is mainly related to uncertainties in the original positioning. It can be concluded with high certainty that the tent lies between 1.8 and 2.5 km from the South Pole.
Keywords: Antarktis; ekspedisjoner; glasiologi; historie

Le tombeau des glaces : duel mortel pour le pôle - Pierre, Marc (Dorval, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Prestrud, Kristian (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1914 - Schröer, Adolf Hermann; Hansen, Ludvig; Rønne, Martin; Hanssen, Helmer; Kutschin, Aleksandr; Wisting, Oscar; Stubberud, Jørgen; Doxrud, Christian; Stubberud, Jørgen; Hansen, Ludvig; Rønne, Martin (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Antarktis : 71 dager, 1800 kilometer og én million tanker - Skog, Cecilie; Sandberg, Sigri (Gyldendal, 2011)
Keywords: Antarktis; Sydpolen; ekspedisjoner; polarekspedisjoner; reiser; reiseskildringer

Overvåking av havklima i Antarktis - Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor (Klima : norsk magasin for klimaforskning, 2011)
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer

Amundsens omstridte forløper ; Innsjøen under isen - Thuesen, Nils Petter (Vi menn vitenskap & historie, 2011)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Vostoksjøen; ekspedisjoner; glasiologi; subglasial innsjø

Clues to historical climate variation and future changes in sea level buried in the Antarctic ice (TASTE-IDEA) - Winther, Jan-Gunnar; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Det Internasjonale polaråret 2007; Dronning Maud Land; glasiologi; havnivåstigning; klimaendringer; polarforskning

Sydpolsekspedisjonen 1910-1912 - Amundsen, Roald (Frammuseet, 2010)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

The South Pole expedition 1910-1912 - Amundsen, Roald (Frammuseet, 2010)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Roald Amundsens sydpolsferd (1910-1912) = Roald Amundsen's South Pole expedition (1910-1912) - Amundsen, Roald; Diesen, Jan Anders; Lund, Harald Østgaard (Norsk filminstitutt, 2010)
Keywords: Antarktis; Fram (skip); Norge; Sydpolen; Sydpolsekspedisjonen; dokumentarfilmer; ekspedisjonsfilmer; oppdagelsesreiser; polarområdene

Race for the South Pole : the expedition diaries of Scott and Amundsen - Amundsen, Roald; Scott, Robert Falcon; Bjaaland, Olav; Huntford, Roland (Continuum, 2010)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; kjeldeskrift; oppdagelsesreiser; polarområdene; polferder

Mindre snø enn forventet i Antarktis - Anschütz, Helgard; Isaksson, Elisabeth (Klima: norsk magasin for klimaforskning, 2010)
Keywords: Dronning Maud Land; glasiologi; is; klima; snø

East Antarctic snow accumulation changes - Anschütz, Helgard; Isaksson, Elisabeth; Müller, Karsten; Winther, Jan-Gunnar; Albert, Mary (Ice and climate news, 2010)
Keywords: Antarktis; glasiologi

Long-range migration of a chinstrap penguin from Bouvetøya to Montagu Island, South Sandwich Islands - Biuw, Martin; Lydersen, Christian; Nico de Bruyn, P. J.; Arriola, Aline; Hofmeyr, Greg G. J.; Kritzinger, Petrus; Kovacs, Kit M. (Antarctic Science, 2010)
We describe a long-range migration of a pre-moulting adult chinstrap penguin from Bouvetøya, a small relatively recently established colony, to the South Sandwich Islands, where large, established colonies of this species reside. The trip lasted around three weeks, covered ∼3600 km, and the time of arrival was consistent with the annual moult. The bird did not travel along the shortest path or along a constant bearing, but instead followed what appeared to be a series of two or three rhumb lines of constant bearing. Small southward and northward deviations from the general path were consistent with local water currents. Travel speeds were high during daylight but decreased at night, suggesting that resting or opportunistic feeding occurred preferentially at night. While long-range winter migrations of chinstraps to feeding areas in the vicinity of distant colonies have been previously described, this is the first observation of such a trip during the period between breeding and moulting, and the first record of an individual actually arriving at one of these distant colonies. This has implications for understanding population structure and management of this important Southern Ocean predator.
Keywords: Bouvetøya; NARE 2007/08; Sør-Sandwichøyene; marin biologi; pingviner; sjøfugler

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Holocene Antarctic climate variability from ice and marine sediment cores: insights on ocean-atmosphere interaction - Divine, Dmitry; Koç, Nalân; Isaksson, Elisabeth; Nielsen, Simon H; Crosta, Xavier; Godtliebsen, Fred (Quaternary Science Reviews, 2010)
Holocene climate variability in the southeast Atlantic sector of the Southern Ocean and Antarctic is assessed and quantified through integration of available marine sediment core and Antarctic ice core data. We use summer sea surface temperature (SSST) and sea ice presence (SIP) reconstructions from two marine sediment cores recovered north (50 °S) and south (53.2 °S) of the present day Antarctic Polar Front (APF), as well as an atmospheric temperature and sea ice proxy from the EPICA ice core from Dronning Maud Land (EDML). We find reasonably good agreement in the timing of climate evolution in the analyzed series. Almost all records show a gradual glacial-to-Holocene climate transition, interrupted by the Antarctic cold reversal around 13 000 cal yr BP, and early Holocene climatic optimum (HCO) at about 11 000 cal yr BP. During the early HCO, the seasonal ice cover retreats to south of 53 °S; it then readvances in the course of the mid- to late Holocene. The maximum winter sea ice edge position during the recent 10 000 years varied mainly within 51–53 °S, with sporadic growth to north of 50 °S, a position similar to that during the last glacial. The onset of the Neoglacial period after ca 4000 yr BP is associated with a steepening of the SSST gradient between the marine core sites, strengthening of the westerlies and cooling in the inland ice sheet. The agreement in timing between elevated SSST during the early HCO and decreased deuterium excess in EDML and other ice cores from different locations in the East Antarctic suggests that the retreat of sea ice during the early HCO and weakening of the APF was a general feature of the East Antarctic climate during that time.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; glasiologi; holocene; iskjerner; klimaendringer; oseanografi; paleoklimatologi

A New Approach for Exploring Ice Sheets and Sub-Ice Geology - Eisen, Olaf; Hofstede, Coen; Miller, Heinrich; Kristoffersen, Yngve; Blenkner, Rick; Lambrecht, Astrid; Mayer, Christoph (Eos Transactions American Geophysical Union, 2010)
Keywords: Antarktis; geofysikk; geologi; innlandsis; seismologi

Hva skjedde med vågehvalen i Antarktis? - Fujise, Yoshihiro; Hatanaka, Hiroshi; Ohsumi, Seiji (Ottar, 2010)
Jakten på de store bardehvalene i antarktiske farvann startet på begynnelsen av 1900-tallet og reduserte bestandene sterkt. Vågehvalen ble mindre utsatt for fangst og fikk kanskje en fordel da de større konkurrentene forsvant? Det japanske forskningsprogrammet JARPA har studert endringer i det marine økosystemet i Antarktis.
Keywords: Sørishavet; kval; marin biologi; økosystemer

Whalers' wives in Vestfold, Norway during the pelagic period - Garmel, Hanne (Whaling and History III : papers presented at a symposium in Sandefjord on the 18th and 19th of June 2009, 2010)
Keywords: Norge; Sørishavet; hvalfangst; kulturhistorie; pelagisk

Polarskipet Antarctics stolte historie. Del 2 - Goldberg, Fred (Polarboken, 2010)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; logistikk

Intraspecific differences in the diet of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Bester, Marthán; Kirkman, Stephen; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2010)
Intraspecific differences in the diets of many species of pinnipeds are to be expected in view of the great differences in morphology, life history and foraging behaviour between the sexes of many species. We examined the diet of the Antarctic fur seal population at Bouvetoya, Southern Ocean, to assess intersexual differences. This was made possible by the analysis of prey remains extracted from scats and regurgitations collected in areas used primarily by one or the other sex. The results indicate that both males and females feed primarily on Antarctic krill Euphausia superba with several species of fish and squid being taken, likely opportunistically given their prevalence. Significant differences were identified in the frequency of occurrence of otoliths in scats and the percentage numerical abundance of the major fish prey species in the diet. Adult males ate a smaller quantity of fish overall, but ate significantly more of the larger fish species. The greater diving capabilities of males and the fact that they are not limited in the extent of their foraging area by having to return regularly to feed dependant offspring may play a role in the differences found between the diets of males and females. Additionally, females might be more selective, favouring myctophids because they are richer in energy than krill. The absence of major differences in the diet between the sexes at this location is likely due to the high overall abundance of prey at Bouvetoya.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; sjøpattedyr

Cruising for krill in the Southern Ocean with G.O. Sars - Iversen, Svein A (Red.); Myklevoll, Sigmund (Red.); Mæstad, Kjartan (Red.); Nøttestad, Leif (Red.) (Institute of Marine Research, 2010)
Keywords: Sørishavet; ekspedisjoner; euphausiacea; forskning; krill; marin biologi; marine økosystemer; plankton; raudåte

Antarctic pioneers : the voyage of the Belgica 1879-99 - Kløver, Geir O (Red.) (The Fram Museum, 2010)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; ekspedisjoner; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

An 860 km surface mass-balance profile on the East Antarctic plateau derived by GPR - Müller, Karsten; Sinisalo, Anna; Anschütz, Helgard; Hamran, Svein-Erik; Hagen, Jon-Ove; McConnell, Joseph R; Pasteris, Daniel R (Annals of Glaciology, 2010)
Snow accumulation and its variability on the East Antarctic plateau are poorly understood due to sparse and regionally confined measurements. We present a 5.3 GHz (C-band) ground-penetrating radar (GPR) profile with a total length of 860 km recovered during the joint Norwegian–US International Polar Year traverse 2007/08. Mean surface mass balance (SMB) over the last 200 years was derived from the GPR data by identifying the volcanic deposition of the Tambora eruption in 1815. It varies between 9.1 and 37.7 kg m−2 a−1 over the profile, with a mean of 23.7 kg m−2 a−1 and a standard deviation of 4.7 kg m−2 a−1. The 200 year SMB estimated is significantly lower than most of the SMB estimates over shorter time periods in this region. This can be partly explained by a SMB minimum in the vicinity of the ice divide. However, it is more likely that a recent increase in SMB observed by several studies is largely responsible for the observed discrepancy.
Keywords: Antarktis; Dronning Maud Land; glasiologi

Land and sea-ice properties in Antarctica: bridging the gap between the ground and satellite measurements in the western Ross Sea region - Rack, Wolfgang; Langhorne, Pat; Haas, Christian; Clavano, Wendy; Gough, Alex; Kruetzmann, Nikolai; Pinchin, James; Riger-Kusk, Mette (Ice and climate news, 2010)
Keywords: Antarktis; Sørishavet; glasiologi; havis; isshelf

Who owns the history of whaling? The norwegian whaling industry and the writing of modern whaling history - Ringstad, Jan Erik (Whaling and History III : papers presented at a symposium in Sandefjord on the 18th and 19th of June 2009, 2010)
Keywords: Norge; Sørishavet; hvalfangst; kulturhistorie; pelagisk

A frozen field of dreams : science, strategy, and the Antarctic in Norway, Sweden, and the British empire, 1912-1952 : a dissertation submitted to the Department of History and the Committee on graduate studies of Stanford University in partial fulfillment of the requirements for the degree of Doctor of Philosophy - Roberts, Peder (Peder William Chellew Roberts, 2010)
Keywords: Antarktis; Norge; historie; norske ekspedisjoner; politikk

Antarktistraktatens effekt på norsk politikk 1959-2009: fra polarimperium på sparebluss til nye utfordringer - og ny giv? - Skagestad, Odd Gunnar (Norsk militært tidsskrift, 2010)
Keywords: Antarktis; politikk

Roald Amundsen: Conqueror of the South Pole - Thyvold, Hans Olav (Font forl., 2010)
ROALD AMUNDSEN (1872-1928), norsk oppdager, polfarer og nasjonalhelt. Det første mennesket som fant og seilte gjennom Nordvestpassasjen, og førstemann til å sette fot på Sydpolen. Norges nasjonalarv er en serie gjennomillustrerte bøker som presenterer våre viktigste og mest kjente nasjonale ikoner. De enkeltstående bøkene tar for seg betydelige skikkelser innenfor kunst og litteratur, vitenskap, idrett og samfunnsliv, men også landets mange naturperler, samt sentrale historiske epoker og kulturuttrykk. Hver for seg gir bøkene en oppdatert innføring for lesere som vil gjøre seg bedre kjent med et gitt tema.
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Genetic identification of Southern Ocean octopod samples using mtCOI - Undheim, Eivind Andreas Baste; Norman, Janette Ann; Thoen, Hanne Halkinrud; Fry, Bryan Grieg (Comptes Rendus. Biologies, 2010)
East Antarctic octopods were identified by sequencing mtCOI and using four analytical approaches: Neighbor-joining by Kimura-2-Parameter-based distances, character-based, BLAST, and Bayesian Inference of Phylogeny. Although the distance-based analytical approaches identified a high proportion of the sequences (99.5% to genus and 88.1% to species level), these results are undermined by the absence of a clear gap between intra-and interspecific variation. The character-based approach gave highly conflicting results compared to the distance-based methods and failed to identify apomorphic characters for many of the species. While a DNA independent approach is necessary for validation of the method comparisons, crude morphological observations give early support to the distance-based results and indicate extensive range expansions of several species compared to previous studies. Furthermore, the use of distance-based phylogenetic methods nevertheless group specimens into plausible species clades that are highly useful in non-taxonomical or non-systematic studies. (C) 2010 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Sørishavet; blekksprut; genetikk; marin biologi; taksonomi

The whaling expedition of the Ulysses, 1937-1938 - Walsh, Quentin R; Capelotti, P J (red.) (University Press of Florida, 2010)
Keywords: Sørishavet; ekspedisjoner; historie; hvalbåter; hvalfangstindustri; hvalindustri; kulturantropologi; norske; sjøfolk; sjømenn